Ta’tsîru Istikhdâmi Washîlah Wordwall Litarqiyati Natâiji al-Lughah al-Arabiyah ladâ at-Thullâbi bi al-Madrasah al-Ibtidâiyyah al-Islâmiyyah al-Ahliyah Insan Cendekia Bangkinang - Amelia, Cindy; Nurhasnah, Nurhasnah; Arsya, Fajriani; Yusra, Oktarina (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The purpose of this study to reveal the Effect of the Use of